Accountability through accounting and reporting lenses: lessons from an awqaf institution in a Southeast Asia country - Yaacob, Hisham; Petra, Saerah; Sumardi, Azimah; Nahar, Hairul Suhaimi (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to review, understand and document the contemporary waqf-S management, financial accounting and reporting practices and to understand relevant drivers behind the current accountability culture in waqf-S, aiming at exploring the intertwined nature of accounting, reporting and the religion of Islam. The accountability literature has been relatively scant on the role played by accounting and reporting in not-for-profit, religious-based organizations and its implications for accountability discourse. Three accountability drivers of regulatory, stakeholders and religious image are tested. It is interesting to research how management, accounting and reporting are being practiced in an Islamic organization setting in a non-Islamic country.